Chamber models in radiobiology - Vyshnevsky, I. M.; Drozd, I. P.; Lypska, A. I.; Foursat, A. D. (Reports of the National Academy of Sciences of Ukraine, 2015)
The possibility of using the chamber models for the description of metabolic processes in mammal's organisms is analyzed. It has been shown that the chamber models have sustainable solutions and can definitely describe the processes in open systems such as living organisms. The 11-chamber model is proposed to describe the kinetics of 137Cs in laboratory rats' organisms. The functions of the cesium isotope retention are experimentally determined for each of the chambers, and then they are used for the theoretical determination of biokinetic constants, which are necessary for the calculation of the absorbed dose in organs and tissues of organisms.